2017
DOI: 10.1080/14606925.2017.1352654
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the critique. Using inclusive formative feedback in face-to-face and online communities of practice to improve knowledge acquisition in design education

Abstract: Design teaching originated as a practice-based activity centred on reviewing the visual for its aesthetic appeal. This process has enabled students to produce opportune visual outcomes that lack research, academic rigour and rely on stylistic imitation of contemporary design trends. We identified that this occurs due to two underlying problems: 1) design pedagogies have developed without solid educational foundation; and 2) assessment remains linked to the end product rather than process. To address these issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Although the learning-by-doing approach of PPBL is valued (Dominici, 2017 ), researchers also raise transferability concerns. It is found that students are in need of support systems to transfer acquired knowledge between multiple projects and contexts (Miceli & Zeeng, 2017 ; Whelan et al, 2017 ; Yuan et al, 2018 ). This can be achieved through learner-centred coaching that shifts the role of the teacher to a coach and mentor, or by fostering peer-learning style migration, in which lower-level students are paired to higher-level students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the learning-by-doing approach of PPBL is valued (Dominici, 2017 ), researchers also raise transferability concerns. It is found that students are in need of support systems to transfer acquired knowledge between multiple projects and contexts (Miceli & Zeeng, 2017 ; Whelan et al, 2017 ; Yuan et al, 2018 ). This can be achieved through learner-centred coaching that shifts the role of the teacher to a coach and mentor, or by fostering peer-learning style migration, in which lower-level students are paired to higher-level students.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the value of critique is pointed out as it establishes tacit knowledge transfer, but it is found that students sometimes find it hard to make this knowledge explicit and are not able to apply it in other contexts (Mohamad et al, 2016 ). Therefore, literature calls for a student support system that will enable them to transfer their learning between and across courses (Miceli & Zeeng, 2017 ), and to support teacher-student interactions through visual means (Ferreira et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally looking at critique as feedback can benefit students on multiple other levels. Students have the opportunity to learn new skills [10] and refine their way of thinking about design [15][16]. However, many instructors did not realize that looking at critiques as a learning moment can have all these impacts.…”
Section: Backgroundsmentioning
confidence: 99%
“…As future practitioners, students must be able to speak about their work, but they must also be able to critically respond to questions and criticism as well as critique the work of their peers. Strategic and systematic integration of peer critique and feedback engages both the cognitive and affective domains of learning, enabling students to emotionally engage with the process as well as think critically about their work and the work of their peers (Dannels et al, 2008; Miceli & Zeeng, 2017; Thiessen, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, they often view the process as stressful and humiliating (Anthony, 1991; Cameron, 2003; Scagnetti, 2017), and note confusing feedback or a lack of constructive criticism (Blair, 2006; Smith, 2011). Emphasis placed on outcomes and artifacts in design education can also cause students to focus on presentations that will please their reviewers, rather than engaging the critique as a learning experience or honest reflection of their ideas and process (Anthony, 1991; Blair, 2006; Cret, 1941; Miceli & Zeeng, 2017; Percy, 2004; Scagnetti, 2017). Furthermore, students who “play the game” or perceive critique as a “performance” are likely to be reluctant to question or engage faculty and reviewers in critical dialogue (Anthony, 1991; Blair, 2006; Megahed, 2018; Schrand & Eliason, 2012).…”
Section: Introductionmentioning
confidence: 99%